Aurora B-dependent phosphorylation of Ataxin-10 promotes the interaction between Ataxin-10 and Plk1 in cytokinesis - Tian, Jie (Sci Rep, 2015)
Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant neurologic disorder caused by ATTCT expansion in the ATXN10 gene. Previous investigations have identified that depletion of Ataxin-10, the gene product, leads to cellular apoptosis and cytokinesis failure. Herein we identify the mitotic kinase Aurora B as an Ataxin-10 interacting partner. Aurora B interacts with and phosphorylates Ataxin-10 at S12, as evidenced by in vitro kinase and mass spectrometry analysis. Both endogenous and S12-phosphorylated Ataxin-10 localizes to the midbody during cytokinesis, and cytokinetic defects induced by inhibition of ATXN10 expression is not rescued by the S12A mutant. Inhibition of Aurora B or expression of the S12A mutant renders reduced interaction between Ataxin-10 and polo-like kinase 1 (Plk1), a kinase previously identified to regulate Ataxin-10 in cytokinesis. Taken together, we propose a model that Aurora B phosphorylates Ataxin-10 at S12 to promote the interaction between Ataxin-10 and Plk1 in cytokinesis. These findings identify an Aurora B-dependent mechanism that implicates Ataxin-10 in cytokinesis.